Pengetahuan Akhlak Sosial Sebagai Upaya Mencegah Tindakan Perundungan di Sekolah - Muhammad, Giantomi; Rozali, Zahra Putri; Erhamwilda, Erhamwilda (LP2M Universitas Islam Ahmad Dahlan, 2025)
The current rampant bullying is accompanied by physical violence, not just verbal. Those who are weak are oppressed by a group of people who feel powerful and have power. There is news circulating on television and social media regarding bullying that leads to death every year. This is a very sad phenomenon amidst Indonesia's hopes of gold in 2045. Therefore, massive efforts are needed to tackle bullying, especially in schools. The aim of this research is to describe knowledge of social morals as an effort to prevent bullying. The research uses a qualitative approach with a case study method. Data sources for students and teachers through interviews, documentation and observation processes. Data analysis techniques through data reduction, data interpretation, data triangulation and data conclusions. The results of the research reveal that the implementation of knowledge of social morals is supported by cognitive, affective and psychomotor understanding in students not to bully, thus assessing it as a form of detrimental negative action. Students take better care of themselves and increase their knowledge of social morals that bind Islamic values ​​in forming an Islamic brotherhood